2007
DOI: 10.1177/00222194070400020801
|View full text |Cite
|
Sign up to set email alerts
|

History as Narrative

Abstract: In this study, we examine the nature and quality of students' comprehension of history. Specifically, we explore whether cognitive-psychological theories developed to capture the comprehension of narrative text can be used to capture the comprehension of history. Participants were 36 students with learning disabilities who had taken part in an earlier study designed to investigate the effects of an interactive instructional intervention in history. The results of the original study supported the effectiveness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 30 publications
1
4
0
1
Order By: Relevance
“…This study supports descriptions of pre-service and practicing teachers who believe in the capabilities of students (Grant, 2003) and use knowledge of their students to identify areas that challenge students and then design effective lessons that help everyone be successful (Monte-Sano & Cochran, 2009). Ample evidence exists that students can think historically and participate actively (Barton & Levstik, 2004;Barton, McCully, & Marks, 2004;Brophy & VanSledright, 1997;VanSledright, 2002aVanSledright, , 2002b, especially students with disabilities (Espin et al, 2007;Okolo, Englert, Bouck, & Heutsche, 2007;Okolo, Ferretti, & MacArthur, 2007), and the four teachers in this study contribute to the literature of such descriptions. Four teachers demonstrated strong curriculum consonance (Thornton, 1988) and confirmed descriptions in literature of experienced secondary social studies teachers who can clearly articulate their beliefs are more likely to implement them (Evans, 1990;Fickel, 2000;Goodman & Adler, 1985;Grant, 2003;Thornton, 1988) and adds to the literature with a description of elementary social studies teaching.…”
Section: Grounding the Findings In Literaturesupporting
confidence: 69%
See 1 more Smart Citation
“…This study supports descriptions of pre-service and practicing teachers who believe in the capabilities of students (Grant, 2003) and use knowledge of their students to identify areas that challenge students and then design effective lessons that help everyone be successful (Monte-Sano & Cochran, 2009). Ample evidence exists that students can think historically and participate actively (Barton & Levstik, 2004;Barton, McCully, & Marks, 2004;Brophy & VanSledright, 1997;VanSledright, 2002aVanSledright, , 2002b, especially students with disabilities (Espin et al, 2007;Okolo, Englert, Bouck, & Heutsche, 2007;Okolo, Ferretti, & MacArthur, 2007), and the four teachers in this study contribute to the literature of such descriptions. Four teachers demonstrated strong curriculum consonance (Thornton, 1988) and confirmed descriptions in literature of experienced secondary social studies teachers who can clearly articulate their beliefs are more likely to implement them (Evans, 1990;Fickel, 2000;Goodman & Adler, 1985;Grant, 2003;Thornton, 1988) and adds to the literature with a description of elementary social studies teaching.…”
Section: Grounding the Findings In Literaturesupporting
confidence: 69%
“…Despite the push for texts to be more considerate, Berkeley, King-Sears, Hott, and Bradley-Black (2014) and Berkeley, King-Sears, Vilbas, and Conklin (2016) found that secondary social studies texts showed only mixed improvement in readability. Although students are more likely to recall material when they read texts that are considerate (Beck, McKeown, Sinatra, & Losterman, 1991;Loxterman, Beck, & McKeown, 1994), and students with learning disabilities demonstrated improved comprehension when textbooks were rewritten to be more considerate (Espin, Cevasco, van den Broek, Baker, & Gersten, 2007;Harniss et al, 2007), few studies address the differences between how teachers use considerate and inconsiderate text in social studies. Crawford and Carnine (2000) found that teachers who use textbooks with inconsiderate text viewed reading their textbooks as a hurdle and devoted their time to helping students decode the text, but those with considerate texts did not always know how to structure class time when they had a considerate text.…”
Section: Challenges and Strategies For Students Who Strugglementioning
confidence: 99%
“…Espin, Cevasco, van den Broek, Baker, and Gersten (2007) described the ability to make causal connections between events as the “cement of the universe” (p. 175) and noted that many students with LD have difficulty making these connections. In history texts, causal connections may be confused when events are not presented in a clear sequence that helps students determine which event preceded the other.…”
Section: The Structure Of Dbrmentioning
confidence: 99%
“…Θ δομι του ςυγκεκριμζνου κειμζνου είναι αιτιακι (αίτιο/ αποτζλεςμα) (Slater, 1992), ζτςι, όπωσ αναφζρουν οι Kendeou, van den Broek, White, & Lynch (2007:31) ο ςχθματιςμόσ των κειμενικϊν αιτιακϊν ςυνδζςεων γίνεται αυτόματα ςτα παιδιά μεγαλφτερθσ θλικίασ και κακοδθγεί τθν κατανόθςι τουσ (Espin, Cevasco, van den Broek, Baker, & Gersten, 2007. Sundermeier, van den Broek, & Zwaan, 2005.…”
Section: επιλογι κειμζνωνunclassified
“…Οι ζρευνεσ τθσ Warsnak (1996) και των Carlson, Alejano, & Carr (1991) (Keenan, Betjemann, & Olson, 2008. Espin, Cevasco, van den Broek, Baker, & Gersten, 2007.…”
Section: α φφλοmentioning
confidence: 99%